Ēḻu niṟaṅṅaḷ : ṟēḍiyōśilpaṅṅaḷ - Gōpināthannāyar, Ṭi. En., 1918- (Sāhityapṟavarttaka Sahakaraṇasaṅghaṃ : [Sales Dept.], Nāṣanal Bukksṯṯāḷ, 1971)
Seven plays originally broadcast by All India Radio in Trivandrum.